Reversible Data Hiding In Encrypted Images Using Improved Encryption Technique - Chelliah, Balika J.; Jagadeesan, J.; Mathur, Sneha; Dutta, Saurav (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Recently more and more attention is paid to reversible data hiding (RDH) in encrypted images, since it maintains the excellent property that the original cover can be loss lessly recovered after embedded data is extracted while protecting the image content‟s confidentiality. All previous methods embed data by reversibly vacating room from the encrypted images, which may be some errors on data extraction and/or image restoration. In this paper we propose a different scheme which attains real reversibility by reserving room before encryption with a traditional RDH algorithm, and then encrypting the data and embedding the data in the encrypted image, which is encrypted using a new proposed algorithm. The proposed method can achieve real reversibility that is data extraction and image recoveries are free of any error.